PEMBELAJARAN REFLEKTIF DALAM MOBILE LEARNING MATEMATIKA - Eny Suryani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
Technological developments affect the way of learning in educational institutions. One of them is e-learning which has begun to be implemented in several higher education institutions. This study discusses the use of technology to improve reflective learning. This study uses quasi-experimental methods to measure reflective learning behavior between students who maximize camera features on smartphones when conducting e-learning and students who don't maximize camera features on smartphones when conducting e-learning. The subjects of the research contain ten classes studying statistics course. The experimental class consisted of 5 classes. The control class consists of 5 classes. Specifically, the teaching material in statistics courses used in the research is the size of the concentration of data and the size of data distribution. Results of the study aimed that the effectiveness of e-learning by using a smartphone camera is better than e-learning without using a smartphone camera. Students with high academic ability are able to show better reflective learning, both on self-reflective and peer-reflective. Students who use smartphone camera when conducting e-learning are able to understand teaching material. Students are able to review their answers, both self-answers or peer-answers, when giving comments on e-learning discussion forums. In addition, these students can enhance their focus on concepts and information provided during mobile learning.